2021
DOI: 10.1038/s41598-021-91977-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcranial direct current stimulation combined with listening to preferred music on memory in older adults

Abstract: Listening to autobiographically-salient music (i.e., music evoking personal memories from the past), and transcranial direct current stimulation (tDCS) have each been suggested to temporarily improve older adults’ subsequent performance on memory tasks. Limited research has investigated the effects of combining both tDCS and music listening together on cognition. The present study examined whether anodal tDCS stimulation over the left dorsolateral prefrontal cortex (2 mA, 20 min) with concurrent listening to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 89 publications
(108 reference statements)
5
22
0
Order By: Relevance
“…As personalized music has shown to impact emotional affect in individuals with dementia, it can be further hypothesized that there may be improvements in cognitive performance following preference-based musical listening. For example, enhanced cognitive abilities were demonstrated in populations of healthy older adults after listening to autobiographicallysalient music [18]. Another study in the review also demonstrated a retention in cognitive performance in individuals with dementia after listening to personalized music [14].…”
Section: Discussionmentioning
confidence: 92%
“…As personalized music has shown to impact emotional affect in individuals with dementia, it can be further hypothesized that there may be improvements in cognitive performance following preference-based musical listening. For example, enhanced cognitive abilities were demonstrated in populations of healthy older adults after listening to autobiographicallysalient music [18]. Another study in the review also demonstrated a retention in cognitive performance in individuals with dementia after listening to personalized music [14].…”
Section: Discussionmentioning
confidence: 92%
“…However, the older adult participants who received stimulation during practice no longer had a motor performance deficit. While the findings from these studies suggest that tDCS may improve motor learning for older adults, other studies show either no benefit or even poorer performance when tDCS is paired with task practice (Mooney et al, 2019;Muffel et al, 2019;Habich et al, 2020;Chow et al, 2021). For example, one study found no benefit of a single session of anodal M1 tDCS as older and young adult participants learned a sequential isometric force task using their non-dominant hand during practice (Mooney et al, 2019).…”
Section: Introductionmentioning
confidence: 85%
“…Relative to our interest in auditory processing, both long- and short-term music engagement in older adults has also been associated with neural and behavioral improvements in sensory and speech processing (e.g., Parbery-Clark et al, 2012 ; Alain et al, 2014 , 2019 ; Bidelman and Alain, 2015 ). In line with the arousal-and-mood hypothesis ( Thompson et al, 2001 ; Husain et al, 2002 ), we have proposed that listening to autobiographically salient music may have the potential to improve short-term performance in certain cognitive domains, including speech processing, by improving positive affect and heightening arousal state ( Chow et al, 2021 ).…”
Section: Introductionmentioning
confidence: 95%
“…Autobiographically salient music (i.e., music evoking salient personal memories), in particular, can evoke strong positive affect and heighten arousal ( Belfi et al, 2016 ). In older adults, music listening can boost various cognitive domains related to memory including autobiographical memory recall ( El Haj et al, 2015 ), working memory (WM) ( Chow et al, 2021 ), and semantic memory ( Bottiroli et al, 2014 ). Relative to our interest in auditory processing, both long- and short-term music engagement in older adults has also been associated with neural and behavioral improvements in sensory and speech processing (e.g., Parbery-Clark et al, 2012 ; Alain et al, 2014 , 2019 ; Bidelman and Alain, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation